The influence of culture in customers’ expectations about the hotel service in latin countries with different human development levels - Franco, Mara (2021)
Due to their dynamic nature and importance in the service process defi nition, customers’ expectations have gained attention from researchers and practitioners, and have been essentially focused in developed countries from the Northern Hemisphere. Still, countries, regard less of the hemisphere, have di erent levels of socioeco nomic development and cultural patterns that can have di erent infl uence on customers’ expectations about a service. In this sense, the main purpose of this research is to understand if culture equally infl uences customers’ expectations about a service in countries with di erent cultural patterns and human development levels. The multigroup analysis using structural equation model ling was used to calculate the regression weights for all the path combinations in the analysis for each proposed group of countries. About 1262 customers from 10 Latin countries were enrolled in this study to determine their expectations about the hotel service and cultural dimen sions. Findings show that cultural dimensions infl uence customers’ expectations about the hotel service di er ently in groups of countries with di erent cultural pat terns and levels of human development. Results also indicate that hotel managers should adapt the service to the level of human development of each group of coun tries when it comes to internationalisation.